Umbilical cord albumin and serum bilirubin as predictive factors for hyperbilirubinemia in term neonates - Shekhar, Manu; Kumar, Vinod; Bhalke, Santosh; Goel, Atul (International Journal of Contemporary Pediatrics, 2020)
Background: Hyperbilirubinemia is one of the common causes of neonatal admission. As clinical evaluation may cause a delay in identification and subsequent initiation of medical therapy, there is a need for the sensitive and inexpensive predictive marker for hyperbilirubinemia in neonates. Measurement of cord albumin and its correlation with the serum bilirubin is one of the noninvasive predictive markers for Hyperbilirubinemia. The present study carried out to know the significance of umbilical cord albumin level as a predictor of neonatal hyperbilirubinemia. Methods: It is a hospital-based prospective cohort study, total 100 healthy term new-borns admitted in the Neonatal Intensive Care Unit, were included in the study as per study protocol over a period of one year. The blood sample was collected from umbilical cord blood for the analysis of bilirubin and albumin, and post 72 hours of life venous blood obtained for estimation of serum bilirubin and albumin along with direct and indirect Coombs test. Results: In this study most of the patients were in the gestational age of 37-38 weeks (71%) followed by 38-40 weeks (27%) and only 1% are >40 weeks. A positive correlation was observed between cord blood bilirubin, serum bilirubin, serum albumin, and cord blood albumin levels. Cord blood albumin was a better marker for neonatal hyperbilirubinemia with a sensitivity of 83%, and a specificity of 48%; as compared to cord blood bilirubin with a sensitivity and specificity of 73% and 39% respectively. Conclusions: From this study, cord blood albumin level was demonstrated as a good predictive marker for neonatal hyperbilirubinemia with a sensitivity of 83.1%. and specificity 48.8%. Hence, cord blood albumin may be used as a non-invasive predictor for neonatal hyperbilirubinemia.